Cognitive styles and stress coping styles in person with chronic pain of spinal column - Kopeć, Małgorzata; Terelak, Jan Felicjan (Studia Psychologica: Theoria et praxis, 2009)
The present study investigated the relationship between cognitive styles (field dependence-independence, reflection-impulsivity, differentiation-abstraction) and coping styles (task-oriented, emotionally-oriented, avoidance-oriented) among chronic spinal pain patients. The analysis showed that field independence correlated positivelly with task-oriented coping style. Impulsivity predicted avoidance-oriented coping style, while differentation predicted emotionally-oriented coping style. The results indicate that there are significant relationships among cognitive styles and coping styles. Task-oriented coping style participants suffering from chronic spinal pain seem to be less disabled than the participants with emotionally-oriented coping styles.